THE ŚHIVA-BUDDHIST CONCEPT IN THE TEMPLE OF SINGHASARI-MAJAPAHIT PERIODS - Wahyudi, Deny Yudo; Munandar, Agus Aris; Setyani, Turita Indah (UI Scholars Hub, 2021)
Religious tolerance, which is now starting to fade, has grown since the past. The Śhiva and Buddhist religious coalition from the Singhasari era to Majapahit might represent its religious tolerance. Several temples, consisting of Jawi, Jago, Panataran and Jabung, seem to reflect the concept of Śhiva-Buddhist. Its Śhiva-Buddhist characteristics could be referred from the textual information, its architecture, and its relief. This study used the analytical method and a historical-archaeology approach. The descriptions of these elements were identified and analyzed to strengthen the opinion of the Śhiva-Buddhist coalition. This study found that the Śhiva-Buddhist concept, as reflected in the Jawi, Jago, Panataran and Jabung temples,emphasizes the phenomenon of the coalition of the two religions during the Singhasari-Majapahit period.